Does the PI3K pathway promote or antagonize regulatory T cell development and function? - Soond, Dalya R.; Slack, Elizabeth C.; Garden, Oliver A.; Patton, Daniel T.; Okkenhaug, Klaus (Frontiers in Immunology, 2012)
Regulatory T cells (Tregs) prevent autoimmunity and inflammation by suppressing the activation of other T cells and antigen presenting cells. The role of phosphoinositide 3-kinase (PI3K) signalling in Treg is controversial. Some studies suggest that inhibition of the PI3K pathway is essential for the development of Tregs whereas other studies have shown reduced Treg numbers and function when PI3K activity is suppressed. Here we attempt to reconcile the different studies that have explored PI3K and the downstream effectors Akt, Foxo and mTOR in regulatory T cell development and function and discuss the implications for health and therapeutic intervention.